Financial Flexibility, Sustainability and Performance: An Empirical Investigation on the BIST Manufacturing Sector (Third Sector Social Economic Review, 2026)
This study aims to examine the impact of financial flexibility levels (Firm Financial Flexibility Index – FFI) on the financial performance of manufacturing firms listed in the BIST Sustainability Index. The analysis covers 21 manufacturing firms included in the index, using panel data from the period 2010 to 2022. Return on Assets (ROA), Return on Equity (ROE), and Tobin’s Q ratio were employed as indicators of financial performance. The FFI values of the firms were calculated based on their year-end financial statements. Data for the analysis were obtained from the Public Disclosure Platform (KAP) and the Finnet database. The study also divides the timeframe into two sub-periods: the pre-pandemic and the pandemic period. In this context, it investigates how the impact of financial flexibility on financial performance shifts during times of uncertainty, such as the COVID-19 pandemic. According to the findings, financial flexibility has a positive and statistically significant effect on both ROA and ROE during the full period, while no significant effect was found on Tobin’s Q ratio. During the pandemic period, the positive influence of financial flexibility on ROA became more pronounced, indicating that a flexible financial structure contributes to firm profitability in uncertain environments. The study highlights that financial flexibility, as a critical factor supporting sustainability, serves as a protective and performance-enhancing asset for firms, particularly in times of crisis.
Keywords: Financial Flexibility; Sustainability; Financial Performance; Environmental, Social and Corporate Management(ESG); Panel Data Analysis